PBX Security and Forensics A Practical Approach - Androulidakis, Iosif I.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
PBX Security and Forensics begins with an introduction to PBXs (Private Branch Exchanges) and the scene, statistics and involved actors. This book discusses confidentiality, integrity and availability threats in PBXs. The author examines the threats and the technical background as well as security and Forensics involving PBXs. The purpose of this book is to raise user awareness in regards to security and privacy threats present in PBXs, helping both users and administrators safeguard their systems.
Introduction -- Confidentiality, Integrity and Availability of Threats in PBX -- PBX Technical Details -- PBX Security -- PBX Forensics -- Conclusions.
Keywords: Engineering; Forensic medicine; Data protection; Telecommunication; Engineering; Communications Engineering, Networks; Systems and Data Security; Security Science and Technology; Forensic Science